The Right To Respect For Family Life: Legal Basis For State Interference - O. Davydova, Nataliya (2021)
This article is dedicated to a theoretical and legal study of the concept of "the right to respect for family life". It is based on legal analysis of Ukrainian legislation and the case law of the European Court of Human Rights. It has been argued that the legal bases for state interference in family life are: 1) interference committed under the law, 2) interference with the interests of the majority in a democratic society, 3) interference to prevent disorder, crime, health, morality , rights and freedoms of other citizens.